Topiramate: Effects on cognition in patients with epilepsy, migraine headache and obesity - Sommer, Barbara R. (SAGE Publications, 2013)
This paper reviews the clinical implications of topiramate (TPM)-induced cognitive deficits in patients with epilepsy, migraine headache, obesity, and in normal populations, followed by reviews of the literature describing the reversal of such deficits upon medication discontinuation. It also discusses animal investigations of TPM’s role of neuroprotection in brain injury. TPM’s most intolerable adverse effects (AEs) are on verbal fluency and reaction time, resulting in high discontinuation rates in patients taking it for epilepsy and migraine headache. However, because TPM is so effective in the treatment of epilepsy and migraine headache, its use is expected to continue. There appears to be greater tolerance of TPM’s cognitive AEs when it is used in the treatment of obesity, perhaps because of the lower doses required. Research attempting to predict the populations most vulnerable to the cognitive effects caused by TPM is ongoing. Studies suggest that one such population may include patients with a past psychiatric history. Slow titration and administration of the lowest possible doses may decrease risk of cognitive deficits.